MAKING A PROFILE BOOK ABOUT MALAY TRADITIONAL FOOD AND DRINKS OF BENGKALIS - Zakiatul Munawarah; Sabri Sabri (INOVISH JOURNAL, 2016)
Abstract :Traditional food is a legacy of culture and heritage from the past which can still be served and tasted today. Since the majority of ethnic in Bengkalis Island is Malay, therefore this island is also familiar with the Malay traditional food. Unfortunately, recently this traditional food is less known by the people â€“ both local, national or international. The research question was â€œIs there a profile about Malay traditional food of Bengkalis in dual languages (English and Bahasa Indonesia)? Meanwhile, the purpose of giving information and maintaining the local traditional cultural heritage of Bengkalis Malay cuisines, the objective of this study was about to make a profile book about Malay traditional food of Bengkalis in dual languages (English and Bahasa Indonesia) as one of Â promotional media to promote Bengkalis tourism towards local and international tourists. The result of this study was a profile book entitled â€œBengkalis Malay Traditional Foodâ€. The method used in this study was descriptive research. It explained what existed and helped to find solution toward the problems. The profile book consists of 30 pages and discusses 5 kinds about Malay traditional food of Bengkalis, such as: Masakan (dishes), Masakan Sepinggan (snacks), Kue Basah (cakes), Kue Kering (biscuits), and Minuman (beverages). The study is expected to give some helps to the local government, especially the Tourism Department, Â with a promotional item in form of profile book to promote local traditional food of Bengkalis for both local and international tourists.Â Keywords: Profile Book, Malay Tradition, Food.